2018
DOI: 10.2147/ijn.s183342
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of wound healing by single-wall/multi-wall carbon nanotubes complexed with chitosan

Abstract: BackgroundImpaired wound healing is commonly associated with many health problems, including diabetes, bedsores and extensive burns. In such cases, healing often takes a long time, which subjects patients to various complications. This study aims to investigate whether single-wall or multi-wall carbon nanotubes complexed with chitosan hydrogel can improve wound healing.Materials and methodsInitially, the effects of the complexes on the viability and functionality of fibroblasts were investigated in engineered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 33 publications
1
27
0
Order By: Relevance
“…Additionally, we demonstrated that the topical application of a chitosan hydrogel enriched with CNT in a mouse wound model accelerated wound closure and enhanced fibrosis of the dermis and epithelialization of the epidermis layer. 20 The utilization of modified MWCNT in the generation of scaffolds with enhanced mechanical and biological properties was reported before by Zhang and colleagues, who showed that these scaffolds were compatible with bone mesenchymal stem cells growth and differentiation, and that they also effectively enhanced bone regeneration in vivo. 21 Furthermore, other modified carbon allotropes, like graphene oxide, incorporated in composite scaffolds of collagen, chitosan, and alginate also demonstrated improvements in their mechanical properties and could serve as promising scaffold for engineered bone tissues.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Additionally, we demonstrated that the topical application of a chitosan hydrogel enriched with CNT in a mouse wound model accelerated wound closure and enhanced fibrosis of the dermis and epithelialization of the epidermis layer. 20 The utilization of modified MWCNT in the generation of scaffolds with enhanced mechanical and biological properties was reported before by Zhang and colleagues, who showed that these scaffolds were compatible with bone mesenchymal stem cells growth and differentiation, and that they also effectively enhanced bone regeneration in vivo. 21 Furthermore, other modified carbon allotropes, like graphene oxide, incorporated in composite scaffolds of collagen, chitosan, and alginate also demonstrated improvements in their mechanical properties and could serve as promising scaffold for engineered bone tissues.…”
Section: Introductionmentioning
confidence: 83%
“…HFF-1 cells were maintained and propagated in a growth medium composed of high glucose DMEM containing 15% FBS and 1% penicillin/streptomycin. The ECTs were generated according to a method described in recent publications by our lab, 20 , 24 which was a modified method from Tiburcy and colleagues. 25 Briefly, DMEM powder was used to prepare 10x DMEM, which was further used to prepare 2x DMEM by dilution in water and the addition of FBS up to 20%.…”
Section: Methodsmentioning
confidence: 99%
“…In another study with CC-72 mice cell line, enhanced wound healing activity was observed when single-wall (SW) or multi-wall (MW) carbon nanotubes were complexed with chitosan, producing conjugates showing an interweaving network of CNTs with the chitosan polymer [ 49 ]. Results revealed 80% of the wounds treated with 1% C-SW-CNTs or 5% CS-MW-CNTs and 60% of those treated with 5% CS-SW-CNTs had more fibrosis compared to the internal control wounds.…”
Section: Application Of Different Nanomaterials In Wound Healingmentioning
confidence: 99%
“…On the 20th day, the wounds covered with the indicated nanocomposite displayed almost complete wound healing, whereas XSi-PU membrane and cotton gauze led to 91% and 81% decreases in wound size, respectively. SWCNTs and MWCNTs complexed with chitosan also improved the re-epithelialization of wounds; the most effective in the healing treatment was the nanocomposite with 1 wt% MWCNTs, due to the increase in the amount of deposited collagen in the wound [ 111 ]. On the other hand, antibacterial PU electrospun nanofibers with CNTs developed via an environmentally friendly approach using ethanol as the dispersion solvent exhibited excellent hemocompatibility and inferior hemolysis percentages, and they were found to be suitable as wound dressing materials [ 112 ].…”
Section: Applications For Antimicrobial Polymeric Nanocomposites With Carbon Materialsmentioning
confidence: 99%